Use Of Internet Among Adolescents In Relation To Gender Biasness And Technostress. - Dhaliwal, Sukhmani (International Journal of Scientific Research and Management (IJSRM), 2016)
The widespread use of modern information and communication technology (ICT) in work life and private life follows in the wake of rapid advances in technology and popularization of different devices and applications, implying fast changes in exposure profiles in the population over the past few decades. Although the Internet frequently has been characterized as male-dominated, recent evidence indicates that the gender gap in Internet use is rapidly diminishing. If more females are using the Internet, then what specific applications do they prefer and do they differ from those of males? This article presents results from a survey assessing gender differences in specific uses of the Internet. The issue of possible negative effects of exposure to ICT has been raised by various groups. Musculoskeletal symptoms and ergonomics in relation to computer use and different input devices have been examined, but also, mental health effects have been considered .The term techno-stress emerged more than two decades ago, to describe stress reactions in relation to computer use. It was suggested that computer use can lead to psycho physiological stress reactions due to occupational strain, and that these reactions can become conditioned to the computer work environment, leading to symptoms associated with computer use